The Role of Health Influencers on TikTok in Shaping Gen Z Consumer Behavior: A Review of Digital Communication Perspectives and Popular Culture - Yosaphat Danis Murtiharso (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the role of health influencers on TikTok in shaping Gen Z's health consumption behavior through the perspective of digital communication and popular culture. The research method used is a qualitative approach with literature study and content analysis, focusing on scientific publications, research reports, and relevant TikTok content. The results show that health influencers use edutainment-based communication strategies by utilizing trends, viral music, and popular culture symbols, so that health messages are more easily accepted by Gen Z. Other findings show that Gen Z not only views health messages as education, but also as part of their social identity and digital lifestyle. This study confirms that the role of health influencers on TikTok can be an effective strategy in health communication, although it still faces challenges such as potential misinformation and the need for collaboration with healthcare professionals.